The role of parents' participation and citizens norms in youth's civic participation - Ahmadu, Talatu Salihu; Don, Yahya; Amzat, Ismail Hussein (Multidisciplinary Journals, 2017)
This study examined the effect of parents’ participation and citizens norms on civic participation of youth. Three hundred and seventy five (375) students from three universities located in the northwest region of Nigeria participated in the study through stratified proportionate method. They completed a questionnaire that anchored on a 5- Likert-scale. This quantitative study administered the instruments in a cross-sectional survey. The SmartPLS 3 software was utilized in analyzing the data collected. The results supported the hypothesized direct effect of parents’ participation, dutiful norms, and engaged norms on students’ civic participation. This suggests a substantial effect, thus extending empirical research in the civic participation sphere.